KONTRIBUSI HASIL BELAJAR MERENCANA STUDIO KRIYA TEKSTIL MODE I TERHADAP KESIAPAN SEBAGAI FASHION DESIGNER - Susanti Supriawati; Mila Karmila (Fesyen Perspektif, 2016)
This study examines the contribution of learning to plan a textile craft studio mode I to readiness as a fashion designer. The purpose of this study was to determine the contribution of learning outcomes plan textile craft studio mode I to readiness as a fashion designer. The method used in this research is descriptive analytic method. The study population are students of the Faculty of Textile and Fashion Craft Creative Industries force Telkom University 2012 which has followed the course plan studio textile craft first mode with a total sample of 40 students with a means of collecting the data in the form of tests and questionnaires. The results showed that the learning outcomes of textile craft studio plan mode I based competency basic concept plan studio textile craft and fashion I, a source of ideas in the form moodboard and craftsmanship as a decorative design are mostly located in the high criteria and provide a significant positive contribution to readiness as fashion designer. Recommendations addressed to students of Textile and Fashion Craft results of this study should serve as a motivation to improve knowledge and skills in the field of textile craft and fashion in order to achieve optimal learning results.